2017
DOI: 10.1016/j.esxm.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Extracorporeal Shockwave Therapy in Sexual Medicine: A Questionnaire-Based Assessment of Knowledge, Clinical Practice Patterns, and Attitudes in Sexual Medicine Practitioners

Abstract: IntroductionLow-intensity extracorporeal shockwave therapy (LI-ESWT) has emerged as a treatment option for male sexual dysfunction. However, results have been contradictory.AimTo investigate the knowledge, practice patterns, and attitudes regarding LI-ESWT among experts in sexual medicine.MethodsA study-specific questionnaire was handed out at the 18th Congress for the European Society for Sexual Medicine. Participants were queried on their knowledge about LI-ESWT and about their use of the equipment.Main Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…DL-ESWT and MSCT have been studied as a treatment of ED for several years [ 45 47 ]. Some findings [ 48 , 49 ] have been used clinically as a novel ED therapy, but translation of MSCT studies to clinic remains slow, and the molecular mechanisms of the effect of LI-ESWT remain confusing [ 50 ]. So we want to provide more theoretic and experimental bases for clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…DL-ESWT and MSCT have been studied as a treatment of ED for several years [ 45 47 ]. Some findings [ 48 , 49 ] have been used clinically as a novel ED therapy, but translation of MSCT studies to clinic remains slow, and the molecular mechanisms of the effect of LI-ESWT remain confusing [ 50 ]. So we want to provide more theoretic and experimental bases for clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recommending Li-ESWT as a treatment option for ED needs to be properly scientifically evaluated, because offering the treatment without evidence carries serious ethical issues. 24 …”
Section: Discussionmentioning
confidence: 99%
“… 18 Results from a recently published survey showed that about 91.2% of experts in sexual medicine would consider the treatment specifically for vasculogenic ED and that 81.6% would combine it with PDE5Is. 23 Preclinical studies have demonstrated that LiESWT can improve DM-associated ED by promoting regeneration of neuronal nitric oxide synthase-positive nerves, endothelium, and smooth muscle in the penis. 24 These beneficial effects appear to be in part mediated by recruitment of endogenous mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%